The Role of Steroid Hormone Receptors in Urothelial Tumorigenesis - Ide, Hiroki (Cancers (Basel), 2020)
Preclinical and/or clinical evidence has indicated a potential role of steroid hormone-mediated signaling pathways in the development of various neoplastic diseases, while precise mechanisms for the functions of specific receptors remain poorly understood. Specifically, in urothelial cancer where sex-related differences particularly in its incidence are noted, activation of sex hormone receptors, such as androgen receptor and estrogen receptor-β, has been associated with the induction of tumor development. More recently, glucocorticoid receptor has been implied to function as a suppressor of urothelial tumorigenesis. This article summarizes and discusses available data suggesting that steroid hormone receptors, including androgen receptor, estrogen receptor-α, estrogen receptor-β, glucocorticoid receptor, progesterone receptor and vitamin D receptor, as well as their related signals, contribute to modulating urothelial tumorigenesis.